Biodegradable tracheal stents: our ten-year experience with adult patients - Stehlik, Ludek; Guha, Debarya; Anandakumar, Sheetal; Taskova, Alice; Vasakova, Martina Koziar (BMC pulmonary medicine, 2024)
BACKGROUND: Biodegradable (BD) stents made from polydioxanone have been used only in human airways. These stents combine the advantages of classical tracheal stents, and fewer side effects are expected due to their biocompatibility and their time-limited presence in airways. However, new clinical consequences have arisen. Here, the authors share their experiences with BD stents for tracheal indications, focusing on their safety and efficacy. METHODS: This was a retrospective review of a collected database of adult patients who underwent implantation of biodegradable tracheal stents between September 2013 and December 2022 at the Department of Respiratory Medicine of the 1st Faculty of Medicine in Prague and Thomayer University Hospital. The indications included functionally significant nonmalignant tracheal stenosis and tracheomalacia. Self-expandable, biodegradable, polydioxanone tracheal stents manufactured by ELLA-CS Ltd. (Hradec Kralove, Czech Republic) were implanted during rigid bronchoscopy under general anaesthesia. All patients were followed up in the department and were provided with the necessary care. The main efficacy and safety parameters and relationships were analysed using descriptive statistics and Fisher ́s exact, Wilcoxon and Kruskal‒Wallis tests. RESULTS: A total of 65 stents were implanted in 47 adult patients. During the first two months after implantation, when adequate function was expected, the stent was found to be effective in 26 out of 39 patients who completed this period (66.7%). The clinical effectiveness reached 89.7%, as early restenoses were mostly mild and necessitated treatment in only 4 patients. The frequencies of significant mucostasis, migration and granulation tissue growth were 2.6%, 7.5% and 23.1%, respectively, during this period. Thirty-four participants completed the half-year follow-up period after the first or second stent insertion, and some were followed up beyond this period. Poor control of symptoms, the development of restenosis and the need for interventions were characteristic of this period as the stents degraded. Twenty-two patients who experienced remodelling or stabilization of the tracheal lumen achieved a stent-free state. Seven patients underwent subsequent surgical treatment. CONCLUSIONS: BD stents are safe and provide adequate tracheal support until they begin to degrade. The use of BD stents necessitates close monitoring of patients and accurate treatment of possible restenosis. TRIAL REGISTRATION: Based on project NT14146 - Biodegradable stents in the management of the large airways (2013-2015, MZ0/NT), registered on May 1, 2013, in the Research and Development and Innovation Information System of the Czech Republic and at ClinicalTrials.gov (reg. no. NCT02620319, December 2, 2015).
Keywords: bronchoskopie; stenty; tracheomalacie; Humans; lidé středního věku; Trachea; Tracheomalacia; vstřebatelné implantáty; Female; Aged; mladý dospělý; dospělí; výsledek terapie; senioři; lidé; Polydioxanone; Prosthesis Design; Absorbable Implants; Adult; Stents; ženské pohlaví; trachea; Male; Middle Aged; Retrospective Studies; Treatment Outcome; Czech Republic; Young Adult; polydioxanon; retrospektivní studie; protézy - design; mužské pohlaví; Česká republika; Tracheal Stenosis; stenóza průdušnice; Bronchoscopy